Effect of grammage on the bonding quality of glue side of Tectona grandis wood - Fonte, Ana Paula Namikata; Trianoski, Rosilani (Revista de Ciências Agroveterinárias, 2015)
Tectona grandis Linn f. wood (teak) is suitable for making Edge Glued Panels (EGP) due to its dimensional stability, physical, mechanical and chemical properties and its resemblance to hardwoods such as mahogany. In generating those products, a highly important variable is the grammage of the adhesive. In this context, this study aimed to evaluate the effect of grammage on the quality of bonded joints of Tectona grandis. To achieve this work teak wood and adhesive polyvinyl acetate were used. The density and the moisture content of the wood were evaluated according to the standard COPANT 461/1972 and 460/1972, respectively, and the chemical properties in accordance with TAPPI standards. The joints were glued using four grammages: 100 g m-2, 140 g m-2, 180 g m-2, and 220 g m-2. The quality of bonding was evaluated by means of shear strength and tested according to EN 13354/2003. The results showed that the mean apparent specific mass was 559 kg m-3, the average moisture content was 7.74% and the total content was 8.27% extractives. The bonded joints showed variation in shear strength of 0.924 MPa to 1.35 MPa for the wet state and 3.01 MPa to 5.43 MPa for dry conditions. There was no statistically significant difference between the averages of the different weights used on the quality of the EGP panels collage. It was concluded that the teak wood had adequate values of properties of wood, glued together had qualified values for the Brazilian standard for shear testing and the best condition was found with a weight of 140 g m-2.